SURPASSING THE SURFACE: AESTHETIC AND PSYCHO-SOCIOLOGICAL IMPLICATIONS OF FLOOR DRAWING ART KALAMEZHUTHU IN KERALA OPHIOLATRY - Nair, Jithesh J.; S., Saran; Panicker, Joji John (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research article titled “Surpassing the Surface: Aesthetic and Psycho-Sociological Implications of Floor Drawing Art Kalamezhuthu in Kerala Ophiolatry” explores the aesthetic sensibilities and psychosociological implications of floor drawing art, Kalamezhuthu, the ritualistic art form in Kerala ophiolatry. It focuses on the profound connections between art, culture, and human experience in the context of performance and folklore. This study unravels the complex interplay of symmetry, colour symbolism, and design principles that define these artworks through a comprehensive analysis of the aesthetic sense embedded in floor art arrangements. By delving into the visual elements and artistic techniques employed in the creation of floor drawing art, the research illuminates how these arrangements serve as a visual language through which spirituality and tradition are expressed and preserved. Moving beyond aesthetics, the paper delves into the psychological implications of engaging with ritualistic floor art, highlighting how these artistic practices and the pictorial effect foster a sense of community, collective identity, and cultural continuity. Furthermore, this study examines the performative aspect of ritualistic floor art drawing, exploring how these artistic practices are embedded in the fabric of daily life and ceremonial occasions in Kerala. By examining the aesthetic and psychosociological dimensions of ritualistic floor art in Kerala, this research underscores the transformative power of art in shaping individual and collective identities, fostering a sense of belonging, and preserving cultural traditions. this study seeks to offer a comprehensive understanding of how ritualistic floor art surpasses its surface beauty to resonate with deeper layers of meaning and significance.